O jogo do cloze : o ensino da leitura com base em estudos cognitivos e metacognitivos - Reis, Marcelo Almeida dos (2020)
This project aims at addressing ways of teaching reading and its self-monitoring strategies through the Cloze technique, assessing 7th graders? reading performance before and after reading workshops are conducted, based on cognitive research. As the theoretical and methodological basis, we adopted some cognitive concepts for reading, which state that reading processing means to read with comprehension. So, if we read to understand, the purpose of reading is comprehension. Hence, one the most important characteristics of reading is the ability the reader possesses to self-regulate their reading comprehension. “The reader must know they are understanding the text well, partially or when it does not make sense” (Leffa, 1996, p. 45). The corpus selected to be analyzed in this project are the answers given by students after some Cloze procedures and activities are conducted, in a 7th-grader class, at a State School, in the city of Muribeca, Sergipe. The methodology applied was a case study since it will assess content on a particular situation. Our guiding question is that the Cloze procedure can impact students positively, boosting them towards a better text comprehension through self-regulated reading. Therefore, the teaching of Portuguese should focus on the importance of self-regulating strategies during the reading process, in order to improve vocabulary, expressiveness and reading automaticity, guiding students towards autonomy and proficiency in reading, based on the latest research on these topics.